Cancer, Fertility Preservation, and Future Pregnancy: A Comprehensive Review - Michelle L. Matthews; Bradley S. Hurst; Paul B. Marshburn; Rebecca S. Usadi; Margaret A. Papadakis; Terry Sarantou (Obstetrics and Gynecology International)
Given the increases in 5-year cancer survival and recent advances in fertility preserving technologies, an increasing number of women with cancer are presenting for discussion of fertility preserving options. This review will summarize the risk of infertility secondary to cancer treatment, available treatment options for fertility preservation, and techniques to reduce future risks for patients. Concerns that will be addressed include the risk of the medications and procedures, the potential delay in cancer treatment, likelihood of pregnancy complications, as well as the impact of future pregnancy on the recurrence risk of cancer. Recent advances in oocyte cryopreservation and ovarian stimulation protocols will be discussed. Healthcare providers need to be informed of available treatment options including the risks, advantages, and disadvantages of fertility preserving options to properly counsel patients.